Storytelling in Siberia : the Olonkho epic in a changing world - Harris, Robin P. (Folklore studies in a multicultural world., 2017)
Significant historical, global, and political forces of the Soviet period undermined the performance practice of the Sakha olonkho epic in northeastern Siberia, impairing the potential for sustainability of this ancient song-story tradition. This work documents how the Sakha people have leveraged UNESCO's 2005 proclamation of this genre as a 'Masterpiece of the Oral and Intangible Heritage of Humanity' in their attempts to revitalize its performance practice.